Proposal for Personal Development Plan for Manager Operating in a Small Company - Bednářová, Zuzana (Vysoké učení technické v Brně. Fakulta podnikatelská, 2022)
Cílem této práce je vytvoření návrhu na rozvoj manažera v soukromém podniku. Prostředkem k tomuto cíli bude vytvoření funkčního kompetenčního modelu, jehož pomocí budu měřit komepence manažera. Teoretická část se zaměřuje na definici manažmentu a funkce manažera, dále definici komepencí a jejích členění. Následně popisuje jednotlivé fáze pro tvorbu kompetenčního modelu a druhy rozvoje vzdělání. Praktická část je zaměřená na popis daného podniku. Poté následuje vytvoření funkčního kompetenčního modelu a jeho praktického ověření. Dalším krokem je měření aktuálních kompetencí manažera, na jehož základě je vytvořen návrh na další jeho vzdělávání.

The aim of this work is a proposal for the development of a manager in a private company. The means will be to create a functional competency model and then measure the manager's competencies. The theoretical part focuses on the definition of management and the manager's function and the definition of competencies and their classification. It then describes the various stages for creating a competency model and types of education development. The practical part is focused on the description of the company. This is followed by creating a functional competency model and its practical verification. The next step is to measure the current competencies of the manager, based on which a proposal for further education is created.
Proposal for Personal Development Plan for Manager Operating in a Small Company
Keywords: Manažment; manažer; rozvoj; kompetence; kompetenční model; klíčové kompetence; plán vzdělání; Národní soustava povolání.; Management; manager; development; competencies; competency model; key competencies; education plan; National system of professions.